The serum‐ & glucocorticoid‐inducible kinase in the regulation of platelet function. (3rd July 2014) - Lang, F.; Gawaz, M.; Borst, O.
Abstract The serum‐ and glucocorticoid‐inducible kinase 1 (SGK1) is expressed in megakaryocytes and circulating platelets. In megakaryocytes, SGK1 activates transcription factor nuclear factor kappa‐B (NF‐κB), which in turn stimulates expression of Orai1, a Ca2+ channel protein accomplishing store‐operated Ca2+ enrty (SOCE). SGK1 enhances SOCE and several Ca2+‐sensitive platelet functions, including degranulation, integrin αIIbβ3 activation, phosphatidylserine exposure, aggregation and thrombus formation. As shown in other cell types, stimulators of SGK1 expression include ischaemia, oxidative stress, hyperglycaemia, advanced glycation end products (AGEs) and a variety of hormones such as glucocorticoids, mineralocorticoids, transforming growth factor beta (TGFβ), interleukin 6 (IL‐6), platelet‐derived growth factor (PDGF), thrombin and endothelin. Thus, SGK1‐sensitive Ca2+ signalling may contribute to altered platelet function in several clinical conditions including inflammation, metabolic syndrome, diabetes mellitus and chronic renal failure. Nevertheless, further studies are needed defining the contribution of altered SGK1 expression and activity to physiology and pathophysiology of platelets.